2014
DOI: 10.1016/j.jped.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in obese children and adolescents

Abstract: The results confirmed that insulin resistance is present in many obese children and adolescents, and that this condition is associated with alterations that represent an increased risk for developing metabolic disorders in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 23 publications
9
44
3
5
Order By: Relevance
“…Insulin resistance is an important condition that is associated with overweight and obesity, and studies have indicated that affected individuals exhibit a higher predisposition for the development of metabolic disorders in adulthood 1,6. An excess of body fat not only results in metabolic changes in adipose tissue and the induction of insulin resistance but also leads to endothelial dysfunction via pro-inflammatory and pro-thrombotic effects due to the action of pro-inflammatory cytokines and adipokines 7.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance is an important condition that is associated with overweight and obesity, and studies have indicated that affected individuals exhibit a higher predisposition for the development of metabolic disorders in adulthood 1,6. An excess of body fat not only results in metabolic changes in adipose tissue and the induction of insulin resistance but also leads to endothelial dysfunction via pro-inflammatory and pro-thrombotic effects due to the action of pro-inflammatory cytokines and adipokines 7.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies assessing cardiometabolic risk markers in overweight children and adolescents show high frequencies of changes in waist circumference (WC), blood pressure, dyslipidemia, insulin resistance and adipokine levels 6,9,10,11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homeostasis model assessment for insulin resistance was calculated based on the formula: HOMA-IR=insulin (mU/L)×glucose (mmol/L)/22.5, and we considered 3 as the cut-off value for the diagnosis of insulin resistance [28].…”
Section: Blood Collection and Biochemical Analysismentioning
confidence: 99%
“…[4][5][6] Indicators of body composition are strongly associated with metabolic changes, and it is important to verify their relationship with components of metabolic syndrome and with insulin resistance. 2,7,8 The body mass index (BMI) is the tool most commonly used to estimate overweight and obesity in children and adults. However, BMI has its limitations because increases may be related to increased fat-free mass.…”
mentioning
confidence: 99%